Mass spectrometry for the evaluation of cardiovascular diseases based on proteomics and lipidomics - Thomas, Aurélien; Lenglet, Sébastien; Chaurand, Pierre; Déglon, Julien; Mangin, Patrice; Mach, François; Steffens, Sabine; Wolfender, Jean-Luc; Staub, Christian (Thrombosis and Haemostasis, 2011)
The identification and quantification of proteins and lipids is of major importance for the diagnosis, prognosis and understanding of the molecular mechanisms involved in disease development. Owing to its selectivity and sensitivity, mass spectrometry has become a key technique in analytical platforms for proteomic and lipidomic investigations. Using this technique, many strategies have been developed based on unbiased or targeted approaches to highlight or monitor molecules of interest from biomatrices. Although these approaches have largely been employed in cancer research, this type of investigation has been met by a growing interest in the field of cardiovascular disorders, potentially leading to the discovery of novel biomarkers and the development of new therapies. In this paper, we will review the different mass spectrometry- based proteomic and lipidomic strategies applied in cardiovascular diseases, especially atherosclerosis. Particular attention will be given to recent developments and the role of bioinformatics in data treatment. This review will be of broad interest to the medical community by providing a tutorial of how mass spectrometric strategies can support clinical trials.
Keywords: Mass spectrometry; proteomics; lipidomics; cardiovascular diseases; imaging mass spectrometry